Bioinspired basalt fiber composites with higher impact resistance through coupling sinusoidal and helical structures inspired by mantis shrimp. (15th April 2023) - Zhang, Binjie; Yang, Jingde; Li, Yujiao; Zhang, Junqiu; Niu, Shichao; Han, Zhiwu; Ren, Luquan
Highlights: A novel laminate composite is designed inspired by mantis shrimp. The bio-inspired laminate composites have extremely high impact resistance. The impact resistance is attributed to sinusoidal structure and helical structure. Helical structure in laminate is mainly responsible for dissipating impact energy. Sinusoidal structure in laminate mainly plays the role of homogenizing stress. Abstract: The imitation of natural and biological structures for the manufacturing of artificial materials provides a series of feasible pathways towards designing materials with excellent mechanical properties for a wide range of applications. Inspired by the dactyl club of mantis shrimps with high-energy absorption and excellent impact resistance, a novel laminate composite is designed and manufactured with basalt fibers through combining sinusoidal fiber structure and helical fiber structure like mantis shrimp. The impact toughness can reach 199.8 kJ/m 2, which is far beyond that of traditional laminates (137.53 kJ/m 2 ). The optimal structural parameters of sinusoidal and helical structures were determined through finite element analysis (FEA) and impact experiments. Combined with the forms of failure, the energy dissipation effect and stress homogenization effect of two structures during impact are researched respectively. Besides, the synergistic effect of sinusoidal and helical structure is investigated in detail. Compared with composites only with single bionic structure, the bio-composites coupling sinusoidal and helical structure have more excellent fracture toughness during impact, owing to the synergy of energy dissipation and homogenization effects ingeniously. Hence, the bio-inspired laminate composites open a broad avenue to explore new generation materials with fascinating mechanical properties through imitating biological structures, which have a great engineering application potential. Graphical abstract: Image, graphical abstract